REALITAS PENGELOLAAN PIUTANG PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN DI KABUPATEN X - Kurniawan, Made Agus; Dwiratnadi, Made; Dwirandra, A.A.N.B (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.10.TAHUN 2017, 2017)
This study aims to reveal the reality of the PBB-P2 receivables management in terms of administration, billing, and write-off account receivables. Exploration understanding of informants using phenomenology as a methodology, with interpretive paradigm as a foothold research. The study's findings that the administration of accounts receivable is constrained by validation and updating data, human resource management, infrastructure, technology mastery, and a lack of understanding of accounting. Collection of accounts receivable PBB-P2 with the system pick up the ball, extend access to payment, and issuing summons for delinquent taxes. Write-off of receivables carried out only limited allowance, but the informant was aware that the receivables that have passed through the billing period should be removed.
Keywords: Accounts, administration, billing, deletion, interpretive, phenomenology.